The Word and the spiritual realities : the I and the Thou : pneumatological fragments - Ebner, Ferdinand, 1882-1931 (The Catholic University of America Press, 2021)
"The first English translation of this seminal work of "dialogic personalist philosophy," in which Ebner argues that human speech is constitutive of human existence: humans receive the word as a miraculous gift from God"--